1993
DOI: 10.1111/j.1574-6968.1993.tb06556.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miconazole on the structure and function of plasma membrane of Candida albicans

Abstract: The primary mode of action of azoles is the inhibition of cytochrome P‐450 dependent 14α‐demethylase, a key enzyme in ergosterol biosynthesis in fungi. Our results demonstrated that Candida albicans cells grown in the presence of 10 μg ml−1 of miconazole (miconazole‐grown), do not possess ergosterol in their plasma membranes and this ergosterol depletion leads to a drastic change in membrane fluidity as shown by fluorescence polarization measurements and unsaturation index. There was an increase in membrane or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Since adhesion to a substrate is an important early step in biofilm formation, lipids that were elevated in early-phase biofilms may be important regulators of fungal adherence in biofilms. In this regard, altered lipid composition is reported to affect Candida adherence (Ghannoum et al , 1986) and nutrient uptake (Ansari & Prasad, 1993; Dudani & Prasad, 1985; Singh et al , 1978). In an early study, Ghannoum et al (1986) showed that lipids from C. albicans and Candida tropicalis , but not from the weakly adherent Candida pseudotropicalis , significantly blocked in vitro adherence of the respective yeast cells to buccal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since adhesion to a substrate is an important early step in biofilm formation, lipids that were elevated in early-phase biofilms may be important regulators of fungal adherence in biofilms. In this regard, altered lipid composition is reported to affect Candida adherence (Ghannoum et al , 1986) and nutrient uptake (Ansari & Prasad, 1993; Dudani & Prasad, 1985; Singh et al , 1978). In an early study, Ghannoum et al (1986) showed that lipids from C. albicans and Candida tropicalis , but not from the weakly adherent Candida pseudotropicalis , significantly blocked in vitro adherence of the respective yeast cells to buccal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since adhesion to a substrate is an important early step in biofilm formation, lipids that were elevated in early-phase biofilms may be important regulators of fungal adherence in biofilms. In this regard, altered lipid composition is reported to affect Candida adherence (Ghannoum et al, 1986) and nutrient uptake (Ansari & Prasad, 1993;Dudani & Prasad, 1985;Singh et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Azoles target essential enzymes of the pathogen's endoplasmic reticulum (ER) that are required for biosynthesis of ergosterol (2,51). A major limitation of these drugs is their inability to directly kill cells of most fungal pathogens (20).…”
mentioning
confidence: 99%
“…The effects of fluconazole on the aspergillus cell membrane are unknown. However, in common with all azoles, fluconazole acts on lanosterol 14‐alpha‐demethylase in the plasma membrane of yeast cells, reducing ergosterol content in the plasma membrane (12, 13), and possibly altering the membrane permeability (14–17). Culture of A. terreus with fluconazole resulted in a modest decrease in GM levels.…”
Section: Discussionmentioning
confidence: 99%